ANALISIS POTENSI PENDAPATAN PAJAK DAERAH DALAM UPAYA PENINGKATAN PENDAPATAN ASLI DAERAH KALIMANTAN SELATAN - NOORHIDAYANTI NOORHIDAYANTI (PPJP Universitas Lambung Mangkurat, 2018)
The purpose of this research is to know the description of the tax area now and to find out how the tax potential of Regions in an attempt to increase Revenue of the original South Kalimantan.The object of this research is in the province of South Kalimantan. Type of this research is quantitative in nature, i.e. data-shaped figures or numbers. The data used in this research is secondary and the data in this study using the method of estimation is to figure out how big the tax potential of regions of the province of South Kalimantan belong to Original income area. The results of this research the potential tax areas of the province in the form of motor vehicle Taxation (PKB), the motor vehicle fuel tax (PBBKB), Customs Tax behind the name of motor vehicle Tax (PBBNKB), surface water (PAP) and taxes of cigarettes owned South Kalimantan very high against the original Revenue areas.Key words: local tax Revenue and the original Area.